Targeting Th17 cells: a promising strategy to treat oral mucosal inflammatory diseases - Wang, Ying; Xue, Ningning; Wang, Ziyuan; Zeng, Xin; Ji, Ning; Chen, Qianming (Frontiers in Immunology, 2023)
With the improved quality of life, oral health is under increased pressure.Numerous common oral mucosal diseases, such as oral lichen planus(OLP) and gingivitis, are related to the destruction of the oral immune barrier. The cytokines secreted by T-helper 17 (Th17) cells are essential for maintaining oral immune homeostasis and play essential roles in immune surveillance. When antigens stimulate the epithelium, Th17 cells expand, differentiate, and generate inflammatory factors to recruit other lymphocytes, such as neutrophils, to clear the infection, which helps to maintain the integrity of the epithelial barrier. In contrast, excessive Th17/IL-17 axis reactions may cause autoimmune damage. Therefore, an in-depth understanding of the role of Th17 cells in oral mucosa may provide prospects for treating oral mucosal diseases. We reviewed the role of Th17 cells in various oral and skin mucosal systemic diseases with oral characteristics, and based on the findings of these reports, we emphasize that Th17 cellular response may be a critical factor in inflammatory diseases of the oral mucosa. In addition, we should pay attention to the role and relationship of "pathogenic Th17" and "non-pathogenic Th17" in oral mucosal diseases. We hope to provide a reference for Th17 cells as a potential therapeutic target for treating oral mucosal inflammatory disorders in the future.